The construct of breast cancer risk perception: need for a better risk communication? - de Jonge, E. T. M. (Facts Views Vis Obgyn, 2009)
Breast cancer risk assessment and communication are much neglected aspects of women’s health care. Breast cancer is the most prevalent cancer-related disease that touches the deepest of a women’s feelings and the subject thus attracts much of the attention of the media. Disease prevalence and media coverage are the roots of inappropriate breast cancer risk perception. Many women overestimate their personal breast cancer risk. Inappropriate risk perception precedes inappropriate health behaviour and it is pivotal to understand the underlying mechanisms in order to plan intervention. Whether interventions such as patient education through counselling and objective risk assessment are effective in restoring inappropriate breast cancer risk perception remains a question unanswered, but the tools to measure breast cancer risk are available and were validated.